IMPACTO DE LA CRISIS FINANCIERA INTERNACIONAL EN EL SECTOR TEXTIL PERUANO - Bautista Flores, Elena Isabel (2010)
Peruvian textile industry slows down from 2009 showing the largest decline recorded in at least 15 years. The collapse of foreign demand in our most important target market -USA, due to international crisis, and the aggressive competition of China in this market. Exports of textile and apparel sector have closed 2009 at US$ 1,550 million, 23% below the level reached in 2008. The most affected segment was the garment that would have made 25%, meanwhile textiles (fibers, yarns and fabrics) would have 15%. In the last months of 2009 there was a growing trend in production costs (cotton yarn) to make finished products more expensive and less competitive against Asian products, characterized by being cheaper but lower quality. In 2010, the Ministry of Foreign Trade and Tourism made important proposals for the Peruvian textile sector: strengthening the chain of cotton-yarn-textile-garment; developing policies to improve the sector’s comparative advantages; use of high-quality Peruvian cotton and reasonable cost: training throughout the chain, and promotion of technological innovation, both for production and adaptation of new seeds to the development of yarn, textiles and garments that are consolidated in the market of high quality. For the year 2010, it has projected a growth of the Peruvian economy by 6.8% and is attributable to a recovery in the international economy, led by emerging economies, and especially by the strong dynamism of domestic demand at first half of 2010. However, for the year 2011 Peruvian economy will maintain the growth projection of 5% due to the uncertainty in the international context and termination of temporary factors that boosted growth in 2010, as the rebuilding of inventories, expansionary economic policy and the rebound effect. If the world economy will not fall down, Peru will grow at rates around 6% for the years 2012 to 2013 for a major private investment projects, also a greater role of emerging countries, strong commodity applicants.